2022
DOI: 10.5858/arpa.2021-0586-sa
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Deaths in Ireland Due to SARS-CoV-2 Placentitis Caused by SARS-CoV-2 Alpha

Abstract: Context.- A severe third wave of COVID-19 disease affected Ireland in the first 3 months of 2021. In this wave, 1 second trimester miscarriage and 6 stillbirths were observed in the Irish population due to placental insufficiency as a result of SARS-CoV-2 placentitis. This observation was at odds with the country's previous experience with COVID-19 disease in pregnant mothers. Objective.- To describe the clinical and pathological features of these pregnancy losses. Design.- Retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…Extensive intervillous fibrin deposition, involving up to 70% or more of the placental tissues in one case, was present in the placentas from all 5 fetuses. Following this report, additional case reports of the placental pathology from stillborn fetuses delivered to mothers with COVID-19 were reported that showed all the placentas to be markedly abnormal and extensively involved with similar destructive features–increased or massive intervillous fibrin deposition, villous trophoblast necrosis, and chronic histiocytic intervillositis [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. In their report of a stillbirth from a mother having COVID-19 at 30 weeks 4 days gestation in Bratislava, Biringer et al [ 80 ] believed the cause of death to be acute placental insufficiency based upon their findings of placental destruction due to SARS-CoV-2 placentitis and an autopsy revealing fetal organs to have no morphological abnormalities.…”
Section: Covid-19 Infection and Stillbirthmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive intervillous fibrin deposition, involving up to 70% or more of the placental tissues in one case, was present in the placentas from all 5 fetuses. Following this report, additional case reports of the placental pathology from stillborn fetuses delivered to mothers with COVID-19 were reported that showed all the placentas to be markedly abnormal and extensively involved with similar destructive features–increased or massive intervillous fibrin deposition, villous trophoblast necrosis, and chronic histiocytic intervillositis [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. In their report of a stillbirth from a mother having COVID-19 at 30 weeks 4 days gestation in Bratislava, Biringer et al [ 80 ] believed the cause of death to be acute placental insufficiency based upon their findings of placental destruction due to SARS-CoV-2 placentitis and an autopsy revealing fetal organs to have no morphological abnormalities.…”
Section: Covid-19 Infection and Stillbirthmentioning
confidence: 99%
“…In addition to individual case reports, there have been reports of cohorts of stillborn fetuses delivered to unvaccinated mothers with COVID-19 that have also demonstrated SARS-CoV-2 placental infection with microscopic findings of SARS-CoV-2 placentitis and fetal death that most probably resulted from placental insufficiency. Analysis of the placentas from the cluster of six perinatal deaths associated with the Alpha (B.1.1.7) variant of SARS-CoV-2 in County Cork (Ireland) [ 78 ] all demonstrated the same severe findings of increased or massive perivillous fibrin deposition, chronic histiocytic intervillositis and trophoblast necrosis—a triad of lesions termed SARS-CoV-2 placentitis by Watkins et al [ 49 ]. Autopsy examination was performed in five cases that showed that all stillborns were anatomically normal with no microscopic evidence that SARS-CoV-2 had affected any fetal organ, and the authors ascribed the fetal deaths as due to placental insufficiency resulting from SARS-CoV-2 placentitis.…”
Section: Covid-19 Infection and Stillbirthmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Among the first cases of fatal fetal death due to placentitis were reports from Irish pathologists, and publicity surrounding this issue, helped ensure high uptake of vaccination among pregnant women. 4 With critical care colleagues, the role of pulmonary endotheliopathy and microvascular immunothrombosis in acute COVID-19 leading to death was described. 5 The significance of symptoms after acute COVID-19 among healthcare staff and their implications were highlighted by occupational health and pathology departments.…”
Section: Response To the Pandemicmentioning
confidence: 99%
“…This notion is supported by a large United States-based cohort of women in which pregnant women infected with SARS-CoV-2 were found to have an increased risk of hospitalization, ICU admission, and mechanical ventilation compared with infected nonpregnant women. Placental insufficiency, miscarriage, and stillbirths resulting from SARS-CoV-2 placentitis have recently been reported in a study on pregnant mothers suffering from COVID-19 ( 9 ). Therefore, special conditions such as pregnancy need to be further evaluated for the effects of COVID-19.…”
mentioning
confidence: 95%